Blood of Martyrs, Seed of Christians: An Analysis of French Catholic Missionary Discourse after the Boxer Uprising, 1900–1910 - Mendoza, Antonio J.
The Boxer Uprising (1898–1901) was an anti-foreign and anti-Christian uprising that culminated in a war against foreigners throughout Northern China during the summer of 1900. Missionary writings have played a prominent role in the writing of the history of the uprising, but the missionary sources employed have been predominantly American, British, and Protestant. In 1992 James L. Hevia, one of the most prominent historians of imperialism in China, presented a discursive history of the uprising, in which he argued that the writing of missionaries after the uprising did not merely seek to represent the events of the uprising but intended to create a history of the event that justified missionary acts of vengeance by placing them within a metanarrative of Boxer atrocity and Western retribution. In this paper, I extend Hevia's analysis to French Catholic missionary writings on the uprising in order to determine whether or not the metanarrative of atrocity and retribution that he identified in Anglophone Protestant missionary writing dominated Francophone Catholic missionary writing as well. This examination reveals a divergence in French Catholic narratives that challenges Hevia's characterization of missionary writing after the Boxer Uprising and the general interpretation of missionary discourse on the Boxer Uprising in modern Chinese historiography.